2013
DOI: 10.1177/0023677213502016
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic evaluation of decapitation of the anaesthetized rat

Abstract: The objective of this study was to evaluate the changes in electroencephalographic (EEG) power spectrum in response to decapitation of anaesthetized rats, in order to assess the nociception or otherwise of this procedure. Ten young adult male Sprague-Dawley rats were anaesthetized with halothane in oxygen and anaesthesia was maintained at a stable concentration of halothane between 1.20% and 1.25%. The rat's head and neck were placed through the opening of a small animal guillotine so that the blade of the gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 21 publications
(41 reference statements)
3
28
0
Order By: Relevance
“…In humans, loss of consciousness is generally accepted to have occurred at the time when the individual is no longer able to engage in verbal communication [6], but this definition is compounded by the fact that humans can engage in significant and appropriate verbal communication with others that is not recalled when under the effect of alcohol or drugs [52,53]. It has been suggested that electroencephalography (EEG) can be used to assess consciousness in animals [1,54,55], but as EEG measurements are present in anesthetized and sleeping animals, this assessment tool is not necessarily as specific as desired [54][55][56]. In animals, the loss of righting reflex is generally accepted as the marker of loss of consciousness [1,6], but again, pinpointing this exact moment is difficult, especially when using gaseous agents where opening the chamber to test the animal affects the concentration and distribution of the gas.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, loss of consciousness is generally accepted to have occurred at the time when the individual is no longer able to engage in verbal communication [6], but this definition is compounded by the fact that humans can engage in significant and appropriate verbal communication with others that is not recalled when under the effect of alcohol or drugs [52,53]. It has been suggested that electroencephalography (EEG) can be used to assess consciousness in animals [1,54,55], but as EEG measurements are present in anesthetized and sleeping animals, this assessment tool is not necessarily as specific as desired [54][55][56]. In animals, the loss of righting reflex is generally accepted as the marker of loss of consciousness [1,6], but again, pinpointing this exact moment is difficult, especially when using gaseous agents where opening the chamber to test the animal affects the concentration and distribution of the gas.…”
Section: Discussionmentioning
confidence: 99%
“…This is a non-invasive and stress free technique and suitable to measure nociception. Therefore, changes in EEG variables of nociception in anaesthetised animals and pain in conscious animals have received much attention (Kongara et al 2010, Kongara et al 2014, Zulkifli et al 2014. Most commonly reported EEG variables in animals are median frequency, spectral edge frequency 95% and total power (Haga and Dolvik 2005, Gibson et al 2007, Murrell et al 2007, Kongara et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, state of disease, drugs used, and personnel expertise in performing the tests used for the confirmation of brain death could influence accurate interpretation of such diagnostic aids . Physiologic, behavioral, and EEG studies have been done in laboratory animals, poultry, piglets, rabbits, dogs, and frogs . Brain activity during euthanasia with intravenous concentrated potassium chloride has been studied by monitoring cerebral blood flow, metabolic state, electrocorticogram, and extracellular ion concentrations in cats .…”
mentioning
confidence: 99%